Morphometric Analysis and Population Genetics of Mahisefid (Rutilus Frisii Kutum Kamensky,1901) in South of Caspian Sea - Abdolhay, Hossein Ali (2010)
Mahisefid is one of the most important and economical fishes in the southern area of the Caspian Sea. The distribution of Mahisefids is from Kura in Azerbaijan to Turkmenistan Republic. Mahisefids migrate to rivers for spawning. The present study aimed to determine morphometric characters, population structure and genetic diversity of Mahisefids. Mahisefid populations were studied from Lamir Rivers and Sefid Rud Rivers in the Guilan Province, as well as Shir Rud Rivers and Tajan Rivers in the Mazandaran Province. A total 387 Mahisefid samples (male and female) were collected in Spring 2005 from four different rivers, where they migrate for their annual migrations. Fourteen conventional morphometrics, 13 ratios morphometric, twelve Truss morphometrics and the ratios to fork length were selected for this study. Conventional and Truss morphometric data of R. frisii kutum from these four rivers were analyzed using two-way ANOVA, discriminant and Principal Component Analysis (PCA). The results showed that all morphometric characters in males and females were significantly different (P<0.05) among the four rivers. Based on conventional morphometric characters there, was no clustering of Mahisefid populations from the fourrivers for both male and female populations,; i.e. However, on the basis of Truss morphometric characters, the pattern of clustering was slightly different in which there was no clustering for male but there was two clusters for female populations. Population of Sefid RudRiver, Shir Rud River and Tajan River populations in one cluster while Lamir river population in another cluster. For RFLP, 294 samples were used and the PCR products were digested by 20 restriction enzymes, namely TasI, HaeIII, HinfI, HincII, SalI, DraI, AccI, AvaII, XhaI, BshNI, AvaI, BclI, BshII, MspI, PstI, RsaI, SdnI, TaqI, TruI, and VspI. The four restriction enzymes namely TasI, HaeIII, HinfI, HincII showed polymorphism, six enzymes did not have any restriction, and 14 enzymes showed monomorphic bands. A total 20 of haplotypes were observed, in which AAAA and BAAA had the highest frequency. The average haplotype frequency of AAAA was 29.93% and the average haplotype frequency of BAAA was 27.55%. Haplotype BDAB was unique for the Sefid Rud River populations, haplotypes ADAA and ABAC were unique for the Lamir River population, haplotype BAAB was unique for the Shir Rud River population while haplotype of BAAC was unique for the Tajan River population. Based on RFLP marker, the four populations of Mahisefid were divided into two main clusters, i.e. Shir Rud River and Lamir River populations in one cluster while Tajan River and Sefid Rud River in another cluster. This clustering was not in accordance to the geographical distance of four rivers populations. In microsatellites analysis, 120 specimens (30 samples from each river) of R. frissi kutum from four rivers were caught. Thirty microsatellite primers were used of which eight primers showed polymorphism. Heterozygosity over all samples was observed among loci that ranged from 0.13 to 0.91. For a given locus, the observed heterozygosity varied greatly among the samples. The highest He was 0.92 at locus SYP4 in Shir Rud River and the lowest He was 0.24 at locus SYP6 in Tajan River. The Fst values between the four rivers were significantly different (P<0.05) suggesting that all of the four populations were significantly differentiated that can be explained by their geographical distances. There were significant deviations (P<0.05) from Hardy-Weinberg Equilibrium at all loci and all rivers except at locus SPY6. The dendogram showed that there were two major clusters in Mahisefid population i.e. The Shir Rud population was in one cluster, while the remaining three populations were in another cluster with a genetic distance value of 0.064. The results of morphometrics, RFLP and microsatellite markers from this study are important to be taken into account by policy markers and fishery managers for stock enhancement program of Mahisefid in Iran. This study also suggested that Mahisefid populations from different river systems should be treated separately since they have different and should not be mixed especially for induce breeding activities.